Direct evidence that late Neanderthal occupation precedes a technological shift in southwestern Italy. Issue 1 (20th July 2022) - Oxilia, Gregorio; Bortolini, Eugenio; Marciani, Giulia; Menghi Sartorio, Jessica Cristina; Vazzana, Antonino; Bettuzzi, Matteo; Panetta, Daniele; Arrighi, Simona; Badino, Federica; Figus, Carla; Lugli, Federico; Romandini, Matteo; et al.
Abstract: Objectives: During the middle‐to‐upper Paleolithic transition (50, 000 and 40, 000 years ago), interaction between Neanderthals and Homo sapiens varied across Europe. In southern Italy, the association between Homo sapiens fossils and non‐Mousterian material culture, as well as the mode and tempo of Neanderthal demise, are still vividly debated. In this research, we focus on the study of two human teeth by using 3D geometric morphometric approaches for a reliable taxonomical attribution as well as obtaining new radiometric dates on the archeological sequence. Material and Methods: This work presents two lower deciduous molars uncovered at Roccia San Sebastiano (Mondragone‐Caserta, Italy), stratigraphically associated with Mousterian (RSS1) and Uluzzian (RSS2) artifacts. To obtain a probabilistic attribution of the two RSS teeth to each reference taxa group composed of Neanderthals and Homo sapiens, we performed and compared the performance of three supervised learning algorithms (flexible discriminant analysis, multiadaptive regression splines, and random forest) on both crown and cervical outlines obtained by virtual morphometric methods. Results: We show that RSS1, whose Mousterian context appears more recent than 44, 800–44, 230 cal BP, can be attributed to a Neanderthal, while RSS2, found in an Uluzzian context that we dated to 42, 640–42, 380 cal BP, is attributed to Homo sapiens . Discussion: This site yields the most recent direct evidence for a Neanderthal presence in southern Italy and confirms a later shift to upper Paleolithic technology in southwestern Italy compared to the earliest Uluzzian evidence at Grotta del Cavallo (Puglia, Italy).